2021
DOI: 10.1111/jre.12909
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of cytotoxic T lymphocyte‐associated antigen 4 (CTLA‐4)‐Ig abrogates alveolar bone resorption in induced periodontitis through inhibition of osteoclast differentiation and activation: An experimental investigation

Abstract: Background/objectives Cytotoxic T lymphocyte‐associated antigen 4 (CTLA‐4) is a critical immunoregulatory molecule expressed on T cells. CTLA‐4 also binds to the surfaces of monocytes and macrophages, precursors of osteoclasts. Research on rheumatoid arthritis demonstrated that CTLA‐4 suppresses inflammation and bone resorption. However, its effects on alveolar bone have yet to be understood. The purpose of this study was to investigate the role and potential mechanism of CTLA‐4 in bone resorption in periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…In the treatment of periodontal disease, the treatment of destruction of the alveolar bone is a major difficulty. Moreover, osteoclasts are the main cells of alveolar bone resorption in periodontitis . Nagai et al performed hydrogel injection to promote periodontal bone regeneration 10 days after ligating the periodontium.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment of periodontal disease, the treatment of destruction of the alveolar bone is a major difficulty. Moreover, osteoclasts are the main cells of alveolar bone resorption in periodontitis . Nagai et al performed hydrogel injection to promote periodontal bone regeneration 10 days after ligating the periodontium.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, osteoclasts are the main cells of alveolar bone resorption in periodontitis. 40 Nagai et al performed hydrogel injection to promote periodontal bone regeneration 10 days after ligating the periodontium. The results also showed that the selfregeneration of bone in periodontitis is limited after the removal of ligature stimuli.…”
Section: Nap Alen/hap Inhibits the Biological Function Of Bmdmsmentioning
confidence: 99%
“…A previous study found that mice lacking the IL‐17 receptor (IL‐17R) are more susceptible to bone loss induced by Porphyromonas gingivalis, thus suggesting that IL‐17 is involved in bone remodeling and homeostasis 43 . The inhibition of osteoclast differentiation and activation abrogates alveolar bone resorption in periodontitis 44–46 …”
Section: Discussionmentioning
confidence: 99%
“…43 The inhibition of osteoclast differentiation and activation abrogates alveolar bone resorption in periodontitis. [44][45][46] In addition, a diagnostic model was constructed for the diagnosis of periodontitis with high sensitivity and specificity and was resorption in periodontal disease. 47 The pocket depth and attachment loss are significantly reduced after treatment with rituximab, thus suggesting that anti-B lymphocyte therapy may be beneficial in improving periodontitis.…”
Section: F I G U R Ementioning
confidence: 99%
“…Periodontitis is a common oral disease associated with chronic pain. Without systemic treatment, the periodontal condition gradually becomes severe, which can lead to excessive alveolar bone resorption, 27 , 28 receding gums, and tooth loss. 29 Otomo-Corgel, et al 30 (2012) and Borgnakke, et al 25 (2013) showed that T2DM patients have distinct microvascular lesions in gingival vessels and a significantly thickened basement membrane.…”
Section: Discussionmentioning
confidence: 99%